2012
DOI: 10.2478/v10136-012-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute poisoning with sarin causes alteration in oxidative homeostasis and biochemical markers in Wistar rats

Abstract: Sarin is a potent inhibitor of acetylcholinesterase (AChE). It is known as an agent of chemical warfare and is one of a number of nerve agents misused for chemical terrorism, e.g. on the Tokyo subway attacks. Though effect of sarin on the cholinergic system is well-known, long-term adverse effects and the role of oxidative stress in sarin toxicity remain unknown. The experiment reported here was carried out on laboratory Wistar rats intramuscularly exposed to 0.5-50% of sarin LD 50 for one hour. A complex bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The inhalation of sarin at levels close to LC 50 can cause increased levels of hypoxia-induced factor-1α, bronchoconstriction, and pro-inflammatory cytokine surges, which alter the lung epithelium, increase bronchosecretions, and can lead to death (Carey et al 2013; Gundavarapu et al 2014). Studies showed that acute sarin poisoning causes changes to the oxidative homeostasis and biochemical markers in rats intramuscularly injected with 50% of sarin LD 50 (Pohanka et al 2012; Abou-Qare and Abou-Donia 2001b). …”
Section: Symptoms and Signs Of Sarin-induced Cholinergic Neurotoxicitymentioning
confidence: 99%
“…The inhalation of sarin at levels close to LC 50 can cause increased levels of hypoxia-induced factor-1α, bronchoconstriction, and pro-inflammatory cytokine surges, which alter the lung epithelium, increase bronchosecretions, and can lead to death (Carey et al 2013; Gundavarapu et al 2014). Studies showed that acute sarin poisoning causes changes to the oxidative homeostasis and biochemical markers in rats intramuscularly injected with 50% of sarin LD 50 (Pohanka et al 2012; Abou-Qare and Abou-Donia 2001b). …”
Section: Symptoms and Signs Of Sarin-induced Cholinergic Neurotoxicitymentioning
confidence: 99%
“…Another group also looked at the effect of oral lipid emulsion in rats following oral exposure to malathion or chlorpyriphos, both lipophilic compounds, in different time points [12] , [101] . Since it was shown in the past that OP exposure leads to oxidative stress [1] , [71] , [92] , [106] , [111] , [140] , this group decided to focus on total antioxidant capacity (TAC) and total oxidant status (TOS) of the rat brain, as well as on immunohistochemical staining of caspase-3 as a marker for apoptosis. In the malathion study, lipid emulsion was given either immediately or with a delay of six and 12 h post-exposure [12] .…”
Section: Ile and Op Poisoningmentioning
confidence: 99%
“…This was suggested by recently-reported reversal of severe OP-induced cardiotoxicity in a human patient by ILE [90] . Mitochondrial protection, antiapoptotic and antioxidant properties: poisoning with OP pesticides in humans and with CWAs in animals are associated with increased oxidative stress [1] , [71] , [92] , [106] , [111] , [140] and with tissue damage, apoptosis and necrosis of cells in the CNS and in other organs [29] , [74] , [87] . Mitochondrial dysfunction in the CNS and other tissues, which was found to occur in OP pesticide poisoning [74] and in nerve-agent exposure [28] , has a causal role in the elicitation of oxidative imbalance and apoptosis.…”
Section: Ile and Op Poisoningmentioning
confidence: 99%
“…The type of drug determines whether hyper-or hypo-glycemia occurs (Sabzghabaee et al 2011;Pohanka, Románek, and Pikula 2012). Long-term hyperglycemia may be involved in many life-threatening complications such as cardiovascular diseases, diabetic nephropathy, neuropathy, and rethinopathy.…”
Section: Introductionmentioning
confidence: 99%